PEMANFAATAN TEKNOLOGI VR DALAM MENCIPTAKAN SENSASI SPATIAL UNTUK MENSIMULASIKAN PENGALAMAN RUANG PADA RUMAH TINGGAL: Utilization Of Vr Technology In Creating Spatial Sensations To Simulate The Experience Of Space In Residential Homes - Adinda Qurota Irani (Jurnal Dimensi Seni Rupa dan Desain, 2023)
The application of Virtual Reality is used as a simulation to provide a virtual space experience. This research is focused on testing the efficiency of Virtual Reality which is used as a medium for interacting with interior space users as an effort to introduce VR as a means to present designs to users to create comfortable spaces. This study uses a qualitative method that focuses on Virtual Reality analysis with a Narrative Research approach because it will provide understanding to users in the form of visual communication which will be realized in the form of VR which is much more accurate so that users will feel more representative, giving a feeling of scale, depth and awareness. spatial. real that cannot be felt by mockups, prototypes, or miniatures. The analysis process in this study is in the form of observation and interviews to find out the user's point of view when using VR as a visual communication tool in viewing works. Then it presents several surveys in the form of open questions to users which will be followed up with secondary research to produce 3D interior simulations realized in VR form. The results of this study are to introduce simulation media for users and interior designers so that they can interact and experience new interior spaces virtually. Keywords: Virtual Reality, space architecture, presentation